A Recent Update on Intranasal Delivery of High Molecular Weight Proteins, Peptides, and Hormones - Sharma, Mayank; Waghela, Simran; Mhatre, Riddhi; Saraogi, Gaurav K. (Current Pharmaceutical Design, 2021)
Proteins and hormones have a wide range of therapeutic uses that have emerged throughout the years. The increase in their clinical application nowadays has outgrown the need to deliver these macromolecules without deterioration. This is where the nasal route of delivery has proven to be the most helpful tool in providing ease of administration. Despite the obstacles, smart polymers, nasal enhancers, nanotechnology-based delivery systems, and computational modeling tools have all been used to increase the nasal route's residence time and absorption window. This review highlights the systemic delivery of macromolecules such as protein and hormones, which can also be delivered via nose-to-brain through various transportation pathways. This strategy has proved beneficial in treating several neurological disorders like brain tumors, Alzheimer's, Ischemic stroke, etc. Except for the marketed preparation and patents, several other drugs are still under clinical trials. We also like to conclude that many of the newer proteins and hormones are still under developmental stages, for which nasal delivery will be a boon in administering these newer molecules.
Keywords: macromolecules